Shaping Purpose-Driven Learning Through Creative Writing - Kalai Vaani Rajandram; Judith Nesamalar Tharumaraj (IAFOR Journal of Education)
Existing literature predominantly emphasizes policy frameworks and technological solutions, neglecting the transformative potential of creative writing in facilitating purpose-driven learning. In the context of advancing Sustainable Development Goals (SDGs), this study addresses the underexplored role of creative writing as a catalyst for societal change and sustainable development. This research seeks to bridge this gap by employing a qualitative methodology that is grounded on a social constructivist model that subsists on focus group conversations and sharing between students and participants that enable the gathering of rich empirical material in the form of narrative responses. The narrative responses are utilized to inspire creative writing initiatives linked to purpose-driven learning. By analysing the impact of creative narratives, poetry, and storytelling on societal perceptions and behaviours, this study aims to uncover the mechanisms through which creative writing influences attitudes towards sustainability and promotes actionable engagement. The anticipated findings intend to showcase the efficacy of creative writing in fostering empathy, encouraging innovative thinking, and amplifying diverse voices, thus providing valuable insights for policymakers, educators, and practitioners involved in sustainable development endeavours.